An introduction to English syntax - Miller, Jim. (Edinburgh : Edinburgh University Press, 2013)
Discusses the central concepts of syntax which are applied in a range of university courses, in business, in teaching and in speech therapy. The book deals with traditional concepts which have been greatly refined and extended since the 1970s, such as what nouns, verbs, adjectives and adverbs are.
Includes index.
Keywords: English language -- Syntax; Language Arts & Disciplines -- Grammar & Punctuation